Reforming the Uniformity of Solid Electrolyte Interphase by Nanoscale Structure Regulation for Stable Lithium Metal Batteries - Zhang, Qian‐Kui; Sun, Shu‐Yu; Zhou, Ming‐Yue; Hou, Li‐Peng; Liang, Jia‐Lin; Yang, Shi‐Jie; Li, Bo‐Quan; Zhang, Xue‐Qiang; Huang, Jia‐Qi (Angewandte Chemie International Edition, 2023)
The stability of high‐energy‐density lithium metal batteries depends on the uniformity of solid electrolyte interphase (SEI) on lithium metal anodes. Rationally improving SEI uniformity is hindered by poorly understanding the effect of structure and components of SEI on its uniformity. Herein, a bilayer structure of SEI formed by isosorbide dinitrate (ISDN) additives in localized high‐concentration electrolytes was demonstrated to improve SEI uniformity. In the bilayer SEI, LiN x O y generated by ISDN occupies top layer and LiF dominates bottom layer next to anode. The uniformity of lithium deposition is remarkably improved with the bilayer SEI, mitigating the consumption rate of active lithium and electrolytes. The cycle life of lithium metal batteries with bilayer SEI is three times as that with common anion‐derived SEI under practical conditions. A prototype lithium metal pouch cell of 430 Wh kg −1 undergoes 173 cycles. This work demonstrates the effect of a reasonable structure of SEI on reforming SEI uniformity.